A transição tecnológica da China e a evolução de seu posicionamento na agenda climática - Câmara, Maria Eduarda Brandão (2021)
China can currently be considered as the engine of world economic growth due to its rapid development and economic and industrial expansion in recent decades. This scenario of growth was also accompanied by a large exploitation of natural resources, environmental destruction and pollution and high energy consumption from coal. The country's position in the environmental discussion was considered disruptive by some authors, for supporting positions characteristic of the discussion on the environment, such as the right to development and the principle of "common but differentiated responsibilities". However, in recent years the country has established robust goals for reducing pollutants and the use of non-renewable energy, introducing low-carbon energy as one of the pillars of its new concept of development. This paper seeks to answer what factors have contributed to the evolution of China's position in the environmental debate. After presenting the central problematic, two factors are attributed to these changes of China’s positioning. The first one is the launching of its great strategy for peaceful rise in 2002 and the second, the increase of the innovative capacities of the country that in the last decades, transitioning from a copying economy based on the use of natural resources, to an innovative economy capable of producing new technologies, including environmental ones. Finally, it is argued in this paper that China, as opposed to having a disruptive position, has undergone a process of evolution of its environmental positioning, supported by its emergence as an economic and technological power.